Retargeting NK‐92 for anti‐melanoma activity by a TCR‐like single‐domain antibody. Issue 10 (8th October 2013) - Zhang, Ge; Liu, Rongzhi; Zhu, Xuekai; Wang, Lei; Ma, Juan; Han, Huamin; Wang, Xiaomin; Zhang, Ganlin; He, Wen; Wang, Wei; Liu, Changzhen; Li, Shenghua; et al.
Abstract : The efficacy of immunotherapy based on natural killer (NK) cells is hampered by intrinsic non‐specific cytotoxicity and insufficient activation of NK cells. Here, we confer the T‐cell receptor‐like (TCR‐like) specificity on NK cells, taking advantage of both the innate and adaptive immune arms of the immune response to generate enhanced anti‐melanoma activity. The TCR‐like antibody (Ab) GPA7 was selected against melanoma‐associated gp100/human leukocyte antigen (HLA)‐A2 complex and then fused to intracellular domain of CD3‐ζ chain. This fusion construct was incorporated into NK‐92MI cell line and expressed as a chimeric antigen receptor on the surface of the cell. The anti‐tumour activity of the transgenic NK‐92MI‐GPA7‐ζ cell line was assessed against melanoma in vitro and in vivo . The engineered NK‐92MI‐GPA7‐ζ cells could recognize melanoma cells in the context of HLA‐A2 and showed enhanced killing of both melanoma cell lines and primary melanoma. Furthermore, adoptively transferred NK‐92MI‐GPA7‐ζ cells significantly suppressed the growth of human melanoma in a xenograft model in mice. Collectively, these results demonstrate that the TCR‐like Ab, GPA7, could redirect NK cells to target the intracellular antigen gp100 and enhance anti‐melanoma activity, providing a promising immunotherapeutic strategy to prevent and treat melanoma.